Media coverage of reports published by the Québec Ombudsman: an automated content analysis - Duval, Dominic; Jacob, Steve; Montigny, Eric; Ouimet, Mathieu (International review of administrative sciences, 2021)
This article examines media coverage of reports published by the Québec Ombudsman, a body that upholds the rights of citizens and that goes by the name of ‘Public Protector’. A large part of the Québec Ombudsman’s mandate is to conduct investigations and issue recommendations following infringements by Québec’s administrative apparatus that affect one or several citizens. These infringements are reported to the ombudsman by citizens, which means that it must be visible to the public. Such visibility relies, to a great extent, on the media, hence the importance of analysing the Québec Ombudsman’s media coverage, a subject that has received little attention in the academic literature. Our article reveals that media coverage of the ombudsman’s reports is inconsistent. We also observe that, on average, newspaper articles adopt a more negative tone than the reports themselves. However, contrary to our expectations, reports with a more negative tone are not necessarily given more media coverage. The best predictor of the presence or absence of media coverage and tone congruence between reports and articles appears to be the presence of a press release issued by the ombudsman. Points for practitioners This article examines media coverage of reports published by the Québec Ombudsman. Based on an automated content analysis, it appears that the media coverage of the reports is not explained by the tone used in the documents published by the Québec Ombudsman. Reports that are more negative are not necessarily given greater coverage by journalists than positive reports. Direct communication efforts with the media (e.g. a press conference and the publication of a press release) are more likely to lead to media coverage.